Perputaran Piutang, Perputaran Persediaan dan ROA Menggunakan Pendekatan DuPont Pada Perusahaan Perdagangan yang Terdaftar di BEI - Lukman, Siti Diva Syarifah; Jusnia, Jusnia (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to determine the effect of accounts receivable turnover and inventory turnover on return on assets (ROA) using the DuPont system approach. The data used in this study are secondary data taken from the Indonesia Stock Exchange (IDX) database, which can be accessed through the official website www.idx.co.id. The independent variables in this study are accounts receivable turnover (X1) and inventory turnover (X2), while return on assets (ROA) is used as the dependent variable. The results showed that (1) accounts receivable turnover partially had a significant positive effect on return on assets (ROA); (2) inventory turnover partially had a significant positive effect on return on assets (ROA).